2009
DOI: 10.1086/599284
|View full text |Cite
|
Sign up to set email alerts
|

Use of a T Cell Interferon-γ Release Assay to Evaluate Tuberculosis Risk in Newly Qualified Physicians in Singapore Healthcare Institutions

Abstract: The high rate of positive baseline TST results in our BCG-vaccinated healthcare workers renders the TST unsuitable as a surveillance tool in this tuberculosis risk group. Use of an IGRA has enabled the detection and treatment of latent tuberculosis in this group. Our T-SPOT.TB conversion rate highlights the need for greater tuberculosis awareness and improved infection control practices in our healthcare institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
5
14
1
Order By: Relevance
“…The twenty-eight students were admitted to the education, engineering, social and information studies, and health science or medicine. These data are consistent with the higher positive ratios for IGRAs reported for international students as compared with medical students in Singapore (4.3%) (Chee et al 2009). On the other hand, the low percentage of LTBI-positive Japanese medical students (< 1%) was consistent with a survey conducted in German nursing students (Schablon et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…The twenty-eight students were admitted to the education, engineering, social and information studies, and health science or medicine. These data are consistent with the higher positive ratios for IGRAs reported for international students as compared with medical students in Singapore (4.3%) (Chee et al 2009). On the other hand, the low percentage of LTBI-positive Japanese medical students (< 1%) was consistent with a survey conducted in German nursing students (Schablon et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…These normal limits of test variability contribute to current thresholds (>10 mm) for skin test conversion (37). Although IGRAs may be more specific than the TST and initially identify fewer persons requiring preventive therapy in some settings (38), subsequent conversions and reversions may occur with greater frequency (7,11,39,40). The reasons for this remain speculative, with possible Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident from recent experiences of North American hospitals that began implementing IGRAs for employee screening after the 2005 Centers for Disease Control and Prevention (CDC) guidelines, which recommended that a change from a negative to a positive IGRA result (using the diagnostic IFN-␥ cutoff of Ն0.35 IU/ml) can be treated as a "conversion" (71)(72)(73)(74). These studies have reported high rates of IGRA conversions and reversions, a phenomenon noted in other studies in settings of low TB incidence as well (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85) (Table 2).…”
Section: Hcws and Serial Testingmentioning
confidence: 95%